Long‐term trends in the distribution, abundance and impact of native "injurious" weeds. Issue 4 (23rd August 2020) - Maskell, Lindsay C.; Henrys, Peter; Pescott, Oliver L.; Smart, Simon M.
Abstract: Questions: How can we quantify changes in the distribution and abundance of injurious weed species ( Senecio jacobaea, Cirsium vulgare, Cirsium arvense, Rumex obtusifolius, Rumex crispus and Urtica dioica ), over long time periods at wide geographical scales? What impact do these species have on plant communities? To what extent are changes driven by anthropogenically induced drivers such as disturbance, eutrophication and management? Location: Great Britain. Methods: Data from national surveys were used to assess changes in the frequency and abundance of selected weed species between 1978 and 2007. This involved novel method development to create indices of change, and to relate changes in distribution and abundance of these species to plant community diversity and inferred changes in resource availability, disturbance and management. Results: Three of the six weed species became more widespread in GB over this period and all of them increased in abundance (in grasslands, arable habitats, roadsides and streamsides). Patterns were complex and varied by landscape context and habitat type. For most of the species, there were negative relationships between abundance, total plant species richness, grassland, wetland and woodland indicators. Each individual species responds to a different combination of anthropogenic drivers but disturbance, fertility and livestock management significantly influenced most species. Conclusions: The increase in frequency and abundance of weeds over decades has implications for landscape‐scale plant diversity, fodder yield and livestock health. This includes reductions in plant species richness, loss of valuable habitat specialists and homogenisation of vegetation communities. Increasing land‐use intensity, excessive nutrient input, overgrazing, sward damage, poaching and bare ground in fields and undermanagement or too frequent cutting on linear features may have led to increases in weeds. These weeds do have conservation value so we are not advocating eradication, rather co‐existence, without dominance. Land management policy needs to adapt to benefit biodiversity and agricultural productivity. Abstract : This study quantifies changes in the frequency and abundance of six pernicious weed species over a 30‐year period. All of the weed species increased in abundance, and negative relationships with indicators of high conservation value have implications for landscape‐scale plant species diversity. A hypothesis‐driven analysis of potential driving variables attributed changes to disturbance, fertility and land management.